Symbolic Self-Gifts: Exploring the Role of Self-Gift Behaviour during the Period of Liminal Transition - DONG, Junming (2017)
Self-gifting is a highly context-bound consumer behaviour, and existing literature has identified the circumstance of significant life transitions is an important context where self-gifting occurs. However, it seems to be no further study investigating self-gift behaviour in this particular context. The present research uses a theoretical lens called "liminality" to explore the self-gift behaviour during individuals' life status transition. Specifically, it examines how self-gifting helps individuals through role transition during the period of liminal transition. The research has been conducted using 13 in-depth interviews embedded with the projective technique. An analytical framework has been proposed for the investigation of consumers' lived experience of self-gifting during the period of liminal transition. The framework integrates the ideas (1) that self-gifts can act as symbolic markers to commemorate significant life transition events, (2) that self-gifting has potentials to act as personal rites of passage positively contributing to individuals' role transition, (3) that self-gifts impact on self-concept redefinition by acting as vehicles for identity reconstruction, (4) that self-gifting copes with liminal state by contribution to psychological well-being. The framework illustrates how self-gifting can contribute to individuals' liminal transition by supporting role transition and redefining the sense of self. The result of the study has enhanced our understanding of self-gift behaviour as well as has given contributions to the literature on consumption during the liminal transition.